Eksperimen pembelajaran matematika dengan strategi numbered head together dansnowball drillingterhadap hasil belajar ditinjau dari keaktifan Siswa kelas viii di smp negeri 1 ngemplakTahun 2015/2016 (Penelitian Eksperimen Kelas VIII Semester Genap Di SMP Negeri 1 Ngemplak Tahun Ajaran 2015/2016) - Setyoningsih, Hana (2016)
The aim of research to describe and analyze: (1) the influence of mathematics learning with the NHT and Snowball Drilling based on the results of learning mathematics, (2) the effect of activity of students towards learning outcomes of mathematics, (3) the interaction between the learning strategies and student activity against the results in mathematics. This research is a quasi experimental with experimental design. The study population was all class VIII SMP N 1 Ngemplak the second semester of the 2015/2016 academic year. The study sample consisted of two classes. The sampling technique using cluster random sampling. The test method usage data collection and documentation. Data were analyzed by analysis of variance with two different cell lines. The results of the data analysis with a significance level of 5% was obtained: (1) there was an effect of NHT and Snowball Drilling on the results of studying mathematics, with F_A = 6.920 (2) no influence activity of students for learning outcomes mathematics, with F_B =81.965 (3) No interaction between the NHT and Snowball Drilling with the activity of students the learning outcomes, with F_AB = 1.591.